ANALYSIS OF SCIENCE LITERACY ABILITY OF JUNIOR HIGH SCHOOL STUDENTS BASED ON PROGRAMME FOR INTERNATIONAL STUDENT ASSESSEMENT (PISA) - Latifatus Sholikah; Faninda Novika Pertiwi (Science Education, Institut Agama Islam Negeri Ponorogo, 2021)
This study aims to analyze the scientific literacy skills of students at MTs N 2 Ponorogo. Science literacy is individual ability to apply the principles of science in everyday life, especially in making decisions and get involved in science issues. This research is fundamental in determining students' scientific literacy skills which are an important ability in facing the challenges of the 21st century. The research method used is qualitative with a naturalistic design. The subjects of this study were 9 students using techniques purpossive sampling. The data collection techniques used were tests and interviews. In addition, science teachers also play a role as supporting subjects. The test in this study used a scientific literacy test adapted from PISA. The test is only on the aspect of scientific competence with indicators explaining scientific phenomena, evaluating and designing inquiry approaches, interpreting data and evidence scientifically. Meanwhile, interviews were conducted in an unstructured manner. Data analysis used Miles and Huberman's model, namely data reduction, data presentation, conclusion and verification. The results showed that students had an average scientific literacy ability of 76.85 in the